2015
DOI: 10.7763/jocet.2015.v3.208
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Regular Waves Propagation and Breaking Using Waves2Foam

Abstract: Abstract-Nowadays, ocean energy has attracted more attention among the researchers due to its massive energy potential. As designing, constructing and testing prototypes are both expensive and time consuming, recently, many researchers have developed numerical wave tanks to simulate the behaviour of the waves as well as the interaction of waves with wave energy converters. This paper aims to model numerical wave tanks, using waves2Foam -a solver within OpenFOAM, to show the propagation of waves, as well as dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The analysis performed by Conde (2019) and the comparisons carried out by Jacobsen (2021) showed that WF does not introduce any spurious reflection in the numerical domain, allowing simulations of longer duration and ensuring the stability of the implemented wave conditions. Furthermore, it has been extensively validated and used for coastal engineering applications, such as water wave propagation and/or wave-structure interactions (El Safti and Oumeraci, 2013;Paulsen et al, 2014a;2014b;Jensen et al, 2014;Chenari et al, 2015;Jacobsen et al, 2015). For these reasons, WF was preferred to the native OF's solver to perform the wave generation in the new CWF code.…”
Section: Reference Solversmentioning
confidence: 99%
“…The analysis performed by Conde (2019) and the comparisons carried out by Jacobsen (2021) showed that WF does not introduce any spurious reflection in the numerical domain, allowing simulations of longer duration and ensuring the stability of the implemented wave conditions. Furthermore, it has been extensively validated and used for coastal engineering applications, such as water wave propagation and/or wave-structure interactions (El Safti and Oumeraci, 2013;Paulsen et al, 2014a;2014b;Jensen et al, 2014;Chenari et al, 2015;Jacobsen et al, 2015). For these reasons, WF was preferred to the native OF's solver to perform the wave generation in the new CWF code.…”
Section: Reference Solversmentioning
confidence: 99%
“…The wave group was extraordinarily well captured during the propagation, shoaling and breaking process. Chenari et al (2015) For better understanding wave properties on the special reef bathymetry, especially the reef slope's affects which is inconvenient and expensive for physical model tests, numerical modelling with Waves2Foam is used to simulate wave propagation over a submerged reef in this present paper. The model is first validated by comparing the numerical results with experimental data.…”
Section: Introductionmentioning
confidence: 99%